'Ahí Batallando': the psychosocial impact of psychosis among Puerto Rican family caregivers. Issue 3 (1st September 2016) - Rivera-Segarra, Eliut; Fernández, Ana Michelle; Camacho-Acevedo, Zulie; Ortiz, Nydia; López-Robledo, Yaritza
ABSTRACT: The provision of care and support to a person living with a psychotic spectrum disorder can have deleterious effects on the health and quality of life of the family caregiver. However, research has neglected to document the impact of the caregiving process on the health of Latino caregivers, particularly Puerto Ricans. The objective of this article is to present the experiences of Puerto Rican carers of people living with a psychotic spectrum disorder. An exploratory qualitative design was used and the study examined the experiences of caregivers attending four family psycho-educational groups in Puerto Rico. Using thematic analysis, three categories were identified as comprising the psychosocial factors theme: (1) burden, (2) social support, and (3) stigma. These findings are discussed in light of the previous literature while taking into account the specific cultural dynamics of the context. Finally, empirically based recommendations to inform future research and interventions with this population are presented.